A Study on the Application of Blended Teaching Model in Integrated English Courses - Jang Xue (Pacific International Journal, 2023)
Since the beginning of the 21st century, blended learning has attracted the attention of scholars. With the influence of the epidemic in the past three years, it is imperative to explore how to apply blended learning to stimulate the impact of the integration of online and offline education in order to achieve the ultimate goal of promoting students’ development. In the foreign language departments of universities in ethnic areas of China, it is significant to conduct teaching practice of the blended teaching model for the course of Integrated English, which occupies a large proportion of the English major curriculum and plays a pivotal role in improving English majors’ language proficiency and cultural literacy. This paper explains the exploration of the blended teaching model in Integrated English in one Chinese independent college in the Inner Mongolia Autonomous Region from two perspectives: the overall design and the analysis of the application of Integrated English I and II. This study collected data from questionnaires, interviews, and teachers’ logs in order to investigate the effect of Integrated English based on the blended teaching model. The analysis of the results indicates that the application of the blended teaching model in Integrated English I and II is conducive to cultivating students’ learning habits, improving their language skills, learning ability, and cultural awareness.